Analisis Evaluasi Strategi Bisnis: Rebranding Wisata TKL Ecopark dengan Metode Boston Consulting Group Matrix dan SWOT - Yeni Winatasari; Martania Dwi Hapsari; Dyah Paramita; Khanin Naima; Yunita Setianingsih; Diah Agustina Prihastiwi (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
The tourism sector is one of the sectors that has an important role in the growth of the regional and national economy so that development is currently being carried out very intensively. TKL Ecopark tourism is one of the tourist attractions that is developing business strategies by rebranding, where it used to have the name Kyai Langgeng Park to become TKL Ecopark. This research was conducted with the aim of evaluating the effectiveness of the new rebranding strategy in increasing revenue. The method used in this research is a quantitative and qualitative approach with data collection techniques using interviews and observation. Meanwhile, the data analysis technique uses the Boston Consulting Group Matrix (BCG Matrix) and SWOT analysis. The research results show that TKL Ecopark has strengths and opportunities in the market to support present and future prospects, but it also has several weaknesses and threats. In addition, the market growth rate increased drastically after the rebranding and relatively good market share. This means that the new business strategy (rebranding) implemented has been effective and efficient in supporting the TKL Ecopark tourist attraction in achieving its goals.